Biomechanical strategies underlying the durability of a wing-to-wing coupling mechanism. (1st July 2020) - Toofani, Arman; Eraghi, Sepehr H.; Khorsandi, Mohammad; Khaheshi, Ali; Darvizeh, Abolfazl; Gorb, Stanislav; Rajabi, Hamed
Abstract: Insects thrived soon after they acquired the ability to fly. Beyond the reach of the non-flying competitors, flying insects colonized a wide variety of habitats. Although flight is an efficient way to disperse and escape predators, it is energetically costly. Hence, various strategies are served to enhance flight efficiency as much as possible. A striking example is the development of wing-to-wing coupling mechanisms in many neopterous insects to minimize the aerodynamic interference of fore and hind wings. However, it remains unclear how the seemingly delicate coupling mechanisms can withstand excessive mechanical stresses encountered during flight. Here we studied the complicated coupling mechanism of drone honey bees, which consists of a set of tiny hooks and a thickened membrane. We found that the durability of the coupling mechanism results from two complementary strategies. First, the angles at which hooks and membrane are coupled and uncoupled may be adjusted, so that the resulting stresses are minimized. Second, the out-of-plane structure, soft base and pronounced tip reduce the stress developed in the hooks, yet maintaining the coupling strength. We anticipate our study, which presents the first numerical model of insect wing coupling mechanisms, to be a starting point for the development of more sophisticated models in the future. Such models are particularly useful for comparative analysis of the influence of different morphological features on the functionality of complex coupling mechanisms. Statement of Significance: Hamuli, or 'tiny hooks', is the Greek term for hook-like structures on the anterior margin of honey bee hind wings. By fitting into the fold posterior margin of fore wings, the hooks couple the two wings to each other. Despite their seemingly fragile structure, the hooks withstand substantial mechanical stresses. We show that the out-of-plane structure, soft base and pronounced tip are morphological features that enhance the durability of the hooks, without compromising their function. Graphical abstract: Image, graphical abstract